How *Not* to Do Survival Research: Reflections on the Bigelow Institute Essay Competition - Augustine, Keith (Journal of Scientific Exploration, 2022)
The recent Bigelow Institute contest rewarding the “best” evidence for life after death epitomizes much of what’s wrong with the current state of survival research, its participants constituting a who’s who list of contemporary survival researchers. Cases that are regularly hyped as among the best evidence for an afterlife are all too often easily susceptible to normal explanations—if only survival researchers would give them a chance. The consistently negative results of 121 years of experimental survival research ought to have spurred soul-searching questions for survival researchers by now. And if we treat discarnate personal survival as a scientific hypothesis, then researchers are rationally obliged to seriously consider biological facts that tell against it, too. Limiting one’s inquiry to attempts to only collect data that might confirm survival is one of the chief hallmarks of pseudoscience, and it’s sadly a feature, not a bug, of the survival literature. This systematic review reveals that survival researchers would better serve science by setting aside their feelings and heeding what the data are telling them, for the probabilities should drive our beliefs, not the other way around. Is discarnate personal survival likely to occur in light of the total available evidence? The overall evidence doesn’t even make personal survival more probable than not.